2019
DOI: 10.3390/ijms20205225
|View full text |Cite
|
Sign up to set email alerts
|

The Mechanisms Underlying the Cytotoxic Effects of Copper Via Differentiated Embryonic Chondrocyte Gene 1

Abstract: Copper is an essential trace element within cells, but it also exerts cytotoxic effects through induction of reactive oxygen species (ROS) production. To determine the mechanisms underlying copper-induced ROS production, we examined the effects of copper sulfate in HeLa cells. Exposure to copper sulfate led to dose-dependent decreases in HeLa cell viability, along with increases in the subG1 and G2/M populations and corresponding decreases in the G1 population. Copper sulfate also increased the levels of apopt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 49 publications
(73 reference statements)
1
13
0
Order By: Relevance
“…We previously reported that ROS production may result in stabilization of HIF-1α [ 31 ]. To determine whether that occurs in OECM-1 or SG cells, we assessed the effects of the ROS scavenger NAC ( Figure 10 ).…”
Section: Resultsmentioning
confidence: 99%
“…We previously reported that ROS production may result in stabilization of HIF-1α [ 31 ]. To determine whether that occurs in OECM-1 or SG cells, we assessed the effects of the ROS scavenger NAC ( Figure 10 ).…”
Section: Resultsmentioning
confidence: 99%
“…Under normal conditions, the Nrf2 activity is suppressed, as it is sequestered in the cytoplasm by binding to Kelch-like ECH-associated protein 1 (Keap1) ( 50 ). It has been reported that CuSO 4 exposure can induce the expression of Nrf2 and downstream gene HO-1 in Hela, HEC-1A, HEK293, and A549 cells ( 16 ). In the present study, CuSO 4 significantly increased the expression of Nrf2 and HO-1 expression in the kidney tissues ( Figures 7E,F ).…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies also reported that the molecular mechanism of Cu nephrotoxicity involved oxidative stress, apoptosis and autophagy, which were characterized by various signaling pathways, including mammalian target of rapamycin (mTOR) pathway, nuclear factor kappa B (NF-κB) pathway, p53 pathway, and the endoplasmic reticulum (ER) stress pathway ( 13 15 ). In in vitro models, CuSO 4 -induced cell death is associated with increases in the levels of senescence, apoptosis, autophagy, mitochondrial damage, and excessive production of reactive oxygen species (ROS) ( 16 ). Recently, Alharbi and colleagues found that turmeric could protect CuSO 4 -induced nephrotoxicity in rats by inhibiting oxidative stress and apoptosis ( 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…The repression of DNA repair pathways despite the induction of DNA damage is still not fully understood; however, Collin and colleagues suggested that cellular senescence may result in repressed DNA repair genes [ 39 ]. An induction of senescence was, so far, shown for copper sulfate in HeLa cells and for Cu NP in Enchytraeus crypticus [ 40 , 41 ]; a potential induction of senescence by CuO NP in mammalian cells remains to be elucidated.…”
Section: Discussionmentioning
confidence: 99%